Rights and Freedoms in the Constitution of 1812 - Pérez Luño, Antonio-Enrique (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
This paper analyses the ideological and philosophical foundations of the fundamental rights established in the Cádiz Constitution of 1812. Special attention is given to the theoretical influence of Jeremy Bentham’s utilitarianism on some of the Parliamentary representatives that participated in the Cádiz Constituent Assembly. The main utilitarian features contained in the 1812 wording are also discussed with detailed accounts of the rights and freedoms granted in the Constitution. Appropriate reference is made to the unsystematic inclusion of fundamental rights, which appear scattered throughout the text. This work presents both an account and an evaluation of the main contributions and limitations that the 1812 Constitution has provided to the origins of Constitutionalism and freedoms in Spanish political history.
Keywords: Constitution of 1812; Jeremy Bentham; Utilitarism; Fundamental Rigths